Fluid mechanics of car exhaust system - Lim, Alton Xin You (Nanyang Technological University, 2022)
This report discusses an investigation on the Exhaust system in cars to reduce losses. The student was introduced to Ansys Fluent software where his duty was to find the optimum configuration of the exhaust system through simulations. Exhaust manifold/header in exhaust system was selected for study based on research findings because it is the key component that will lead to significant improvements in the exhaust system. This report focuses on preliminary findings, research gaps, results and discussion and conclusions. The report highlights the use of the honeycomb structure to reduce turbulence intensity and create a pressure differential that provides an advantage to the exhaust system. ANSYS Fluent software was used to simulate the exhaust gases flow with boundary conditions. The Shear Stress Transport (SST) K-Omega model was used, with the exhaust gases modelled as air. The exhaust header model chosen is from Honda Civic 1.5T with dimensions based on available online sources. Solidworks software was used to create the honeycomb structure and model for simulation. Simulation studies were performed on the model to select the best cell shape based on important parameters and finally, modify the cell size and length to achieve the best result. Illustrations and graphical methods generated by the simulation were used to better interpret the pressure and turbulence intensity. Moreover, with plots and data gathered, the report is concluded with a discussion and understanding of the results.